SuperCert - An Anti-Fraud Identity Intelligence Blockchain Solution for Educational Certificates - Akanksha Gairola,; Amira Shaikh,; Shriya Salian,; Shankar Malve,; Mr. Pravin Jangid, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
In recent years, the proliferation of fraudulent educational certificates has posed significant challenges to academic institutions, employers, and individuals alike. Such certificates not only undermine the credibility of educational achievements but also jeopardize the integrity of various industries. To combat this issue, this research introduces SuperCert, an innovative anti-fraud identity intelligence blockchain solution tailored for educational certificates. SuperCert leverages blockchain technology to establish a decentralized, immutable ledger that securely stores educational credentials. The system incorporates smart contract functionality to automate verification processes, thereby reducing administrative overhead and enhancing efficiency.
Keywords: Transcript; Verification; Authentication; Confidentiality; Blockchain; Smart Contract; IPFS; Ethereum; Metamask; University